1990
DOI: 10.1105/tpc.2.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Role of propeptide glycan in post-translational processing and transport of barley lectin to vacuoles in transgenic tobacco.

Abstract: Mature barley lectin is a dimeric protein composed of two identical 18-kilodalton polypeptides. The subunits of barley lectin are initially synthesized as glycosylated proproteins, which are post-translationally processed to the mature protein preceding or concomitant with deposition of barley lectin in vacuoles. To investigate the functional role of the glycan in processing and intracellular transport of barley lectin to vacuoles, the sole N-linked glycosylation site residing within the COOH-terminal propepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 45 publications
2
62
0
1
Order By: Relevance
“…In support of this hypothesis is the fact that retention of the vacuolar pea vicilin protein in the ER by engineering a ER retention signal onto the protein stabilized the modified protein 100-fold over unmodified vicilin protein when synthesized in leaves of transgenic plants (Wandelt et al, 1992). However, many vacuolar proteins such as the pea lectin (Edwards et al, 1991), barley lectin (Wilkins et al, 1990), and cowpea trypsin inhibitor (Hilder et al, 1987) have been shown to be stable in leaves of transgenic plants. Thus, it follows that the stability of a protein is not determined solely by its subcellular location but may be controlled by the intrinsic properties of the protein itself.…”
mentioning
confidence: 84%
“…In support of this hypothesis is the fact that retention of the vacuolar pea vicilin protein in the ER by engineering a ER retention signal onto the protein stabilized the modified protein 100-fold over unmodified vicilin protein when synthesized in leaves of transgenic plants (Wandelt et al, 1992). However, many vacuolar proteins such as the pea lectin (Edwards et al, 1991), barley lectin (Wilkins et al, 1990), and cowpea trypsin inhibitor (Hilder et al, 1987) have been shown to be stable in leaves of transgenic plants. Thus, it follows that the stability of a protein is not determined solely by its subcellular location but may be controlled by the intrinsic properties of the protein itself.…”
mentioning
confidence: 84%
“…Although other plant proteins have been expressed and shown to be correctly processed in transgenic tobacco (Hoffman et al, 1987;Sturm et al, 1988;Sonnewald et al, 1989;Wilkins et al, 1990), expression of heterologous proteins in this system sometimes results in accumulation of molecular forms not normally observed in the native tissue (Higgins et al, 1988;Post-Beitenmiller et al, 1989;Altabella and Chrispeels, 1990). It is, therefore, significant that polygalacturonase, whose complex maturation process includes core glycosylation, oligosaccharide modification, and at least three proteolytic processing steps, appears to undergo identical processing events in the transgenic host, including the heterogeneous reactions associated with maturation of the PG2A and PG2B isozymes.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisomal targeting was amino termini (Subramani, 1992;van den Bosch et ai., 1992). In adeletional analysis of the propeptide that contains ayeast vacuolar targeting signal, QRPL, Johnson et al (1987) found All barley lectin (BL) mutant carboxyl-terminal propeptide (CTPP) constructs were prepared by site-specific mutagenesis as described by ther by modification of the CTPP coding region of the wild-type clone described by Wilkins et al (1990) or by the addition of specific nucleotide sequences between the final codon for the mature Drotein and ako mediated by different signals 'Ocated at the carboxy and et ai. (1990).…”
Section: Preparation Of Bl-mutant Ctpp Constructsmentioning
confidence: 99%